New low-dose liquid pilocarpine formulation for treating dry mouth in Sjögren's syndrome: clinical efficacy, symptom relief, and improvement in quality of life - Machiko Watanabe; Chisato Yamada; Yoshinori Komagata; Hirotoshi Kikuchi; Hiroyuki Hosono; Fumio Itagaki (BMC, 2018)
Abstract Background Patients with Sjögren's syndrome (SS) typically present clinically with xerostomia (dry mouth) because of progressive damage to the exocrine glands. We developed a new, low-dose pilocarpine/sodium alginate (LPA) solution with pilocarpine hydrochloride to inhibit systemic adverse effects by administering via the oral mucosa. The purpose of this study was to assess its stability, safety, and efficacy. Methods The pilocarpine concentration in an LPA liquid formulation was measured 3, 7, 14, and 28 days after preparation to assess its stability. A prospective clinical trial was undertaken to assess the efficacy and safety of the LPA solution as a symptomatic treatment for dry mouth in SS. Patients (n = 24) with clinically significant xerostomia were enrolled after providing written informed consent. Whole-mouth salivary flow rate was measured twice; immediately before and 60 min after LPA application. Symptoms were assessed by questionnaire with visual analog scales or checkboxes before the first application (baseline), and then once daily for 7 days. Results The pilocarpine content 3, 7, 14, and 28 days after preparation showed no marked change, confirming its stability. Salivary flow was significantly increased from 0.076 ± 0.092 g/30 s to 0.122 ± 0.140 g/30 s 60 min after LPA administration (P < 0.001). Dry mouth and thirstiness showed significant improvement compared with that of baseline (P ≤ 0.01). The only adverse effect was sweating, and no serious drug-related adverse events were reported. Conclusions This new, low-dose pilocarpine formulation was well-tolerated and resulted in significant improvements in symptoms of dry mouth and other xerostomic conditions in patients with SS. Trial registration The study approval number in the institution; 08-068-2. Registered January 19, 2009. UMIN000029307. Registered 27 September 2017 (retrospectively registered).